Linking people and activities through community mobility: an international comparison of the mobility patterns of older drivers and non-drivers. Issue 8 (30th August 2022) - Unsworth, Carolyn; Dickerson, Anne; Gélinas, Isabelle; Harries, Priscilla; Margot-Cattin, Isabel; Mazer, Barbara; Stapleton, Tadhg; Swanepoel, Lizette; Timmer, Amanda; Niekerk, Lana Van; Vrkljan, Brenda
Abstract: Community mobility using private and public transportation is important for maintaining health, social participation and living well in later life. This international cross-sectional cohort study (N = 246) reported on the health and driving status of older adults from seven countries where the mobility patterns of drivers and non-drivers were compared in terms of city and rural areas, weather, as well as their respective differences in the number of out-of-home places accessed and quality of life. Older adults participated in a semi-structured interview and completed four standardised instruments: the EQ-5D-5L, modified PULSES health profile, modified Transportation Questionnaire, and the Transport – Participation in Activities and Places Outside the Home. Results suggested inclement weather and place of residence negatively impacted out-of-home activities but did not increase use of public transportation. Drivers accessed more out-of-home activities than non-drivers, suggesting higher community participation among this group, and quality of life was generally high among all participants, but slightly higher for drivers. Findings indicate that a complex myriad of factors can influence community mobility in older adults and further investigations are needed to understand patterns of transport in later life, particularly with regard to those factors that promote and maintain transport mobility, and relationships between transport mobility, community participation and quality of life.